"Count on me" Program to improve school coexisting in primary education. (August 2021) - Pina, David; Ruiz-Hernández, José Antonio; Llor-Esteban, Bartolomé; Matás-Castillo, Mercedes; Pagán-Escribano, María; Puente-López, Esteban
Highlights: Behavioural problems in adolescents are common in schools. This is the first efficacy study of a programme that combines attitude modification and peer mediation. The programme is effective for both antisocial and prosocial behaviour. It is a cost-effective programme within the reach of any school. Abstract: Background: After the family, school is the most important system of interpersonal relationships and socialization for children. Acceptance or rejection in the peer group, as well as relationships with the models of authority represented by teachers and parents, have profound consequences on children's subsequent emotional and social development, depending on whether relationships are based on respect or violence. Achieving a safe school environment is a challenge and a need for children's adequate psychosocial development. Objective: The objective of this research is to analyze the effectiveness of an intervention program to improve school coexistence in Primary Education, based on its effects on the perception of the frequency of antisocial and prosocial behaviors among peers. Participants and settings: The subjects of the study were 256 Primary Education children aged between 9 and 12 years (145 in the experimental group and 111 in the control group). Methods: This study used a quasi-experimental design with control group. All participants completed a protocol that included sociodemographic data, cohabitation issues, five self-administered questionnaires, and a question on sincerity in the pretest and posttest phases. The intervention with the experimental group consisted of a module of eight face-to-face sessions and a peer mediation module throughout the entire academic year. Results: The results show a change in the trend of perceived violence. The groups, initially different (A higher rate of antisocial behaviors in the experimental group), were similar after the decrease in the intervention group's antisocial behavior indicators. The initially similar indicators of prosocial behavior varied, increasing significantly in the experimental group. Conclusions: These findings support the need to incorporate into primary education awareness and reflection on the concept of violence, as well as the habit of alternative reactions to violent behavior, through social dialogue procedures and peaceful conflict resolution.